Job stress and coping of Filipino employees in locally-managed and foreign-managed outpatient veterans facilities - Soriano, Twinky Yu.
This particular study compares job stressors, job stress levels, and coping responses among two groups of Filipino employees: one group working in a locally-managed outpatient veterans clinic and the other working in a foreign-managed facility. The analytical framework of the study argues that stress is a universal phenomenon. To document and analyze its findings, the comparative survey design is used by the study. A three-part survey questionnaire is the instrument generated the socio-demographic and job-related characteristics (Appendix D). The second part was used to document the Job Stress Profile of the respondents (Appendix F). This was adapted from Rice (1992). And the third part adapted from Greenglass, Schwarzer & Taubert (1999) documented the Proactive Coping Inventory (PCI) of the respondents (Appendix H). The findings of the study reveal that there is no significant difference between the two groups in the interpersonal type of job stressors. However, significant differences when noted in the physical conditions and job interest and involvement categories of job stressors affecting the two groups of respondents. Physical conditions and the job interest and involvement type of stressors were causing more job stress to the respondents at the foreign-managed facility than those in the locally-managed one. The respondents from the foreign-managed facility were found out to be experiencing higher levels of job stress compared to those working in the locally-managed facility. This finding is supported by the high stress level scores gathered from three types of job stressors namely: interpersonal, physical conditions and job interest and involvement. There was no significant difference noted in the types of coping responses being utilized by both groups of employees. In short, the respondents from both facilities were roughly utilizing the same coping responses when beset by stressors.
Thesis (M.A. Nursing)--University of the Philippines Manila.
Keywords: Veteran's hospitals -- Outpatient services -- Philippines; Philippines -- Officials and employees -- Job stress